2006
DOI: 10.1007/s10658-006-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR for Quantification of Toxigenic Fusarium Species in Barley and Malt

Abstract: A real-time PCR technique was applied for the quantification of trichothecene-producing Fusarium species (TMTRI assay) as well as the highly toxigenic Fusarium graminearum (TMFg12 assay) present in barley grain and malt. PCR results were compared to the amounts of trichothecenes detected in the samples to find out if the PCR assays can be used for trichothecene screening instead of expensive and laborious chemical analyses. DNA was extracted from ground kernels using a commercial DNA extraction kit and analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 25 publications
2
29
2
Order By: Relevance
“…Sarlin et al (2006) on Finnish barley and malt grain samples which contained relatively low DON levels. Low DON production in our samples can be explained due to strong dependence on the toxin production by such factors, as grain microflora, temperature, humidity, etc.…”
Section: Tablementioning
confidence: 99%
“…Sarlin et al (2006) on Finnish barley and malt grain samples which contained relatively low DON levels. Low DON production in our samples can be explained due to strong dependence on the toxin production by such factors, as grain microflora, temperature, humidity, etc.…”
Section: Tablementioning
confidence: 99%
“…However, some authors have reported a positive correlation between the PCR detection of DNA from Fusarium culmorum and the presence of nivalenol in cereal samples (Pasquali et al, 2010). Also, Sarlin et al (2006) have reported a correlation between the F. graminearum DNA level and the deoxynivalenol content in north American barley and malt samples. A positive PCR result for mycotoxigenic Alternaria speciesgroups can therefore be taken as an indication of the use of low quality raw materials, and also the potential presence of Alternaria mycotoxins in the final products that should be analyzed further.…”
Section: Analysis Of Commercial Samplesmentioning
confidence: 99%
“…A positive correlation between the PCR detection of fungal DNA and mycotoxins has been reported for Fusarium culmorum and the presence of nivalenol in cereal samples (Pasquali et al, 2010). Also, Sarlin et al (2006) reported a correlation between Fusarium graminearum DNA concentration and the deoxynivalenol content in North American barley and malt samples.…”
Section: Type Of Product (No Samples)mentioning
confidence: 83%